Clinical risk factors for sarcopenia in acute and chronic pancreatitis - Mitchell L. Ramsey; Andrew Lu; Kristyn Gumpper-Fedus; Stacey Culp; David Bradley; Darwin L. Conwell; Zobeida Cruz-Monserrate; J. Royce Groce; Samuel Han; Somashekar G. Krishna; Peter Lee; Thomas Mace; et al. (BMC Gastroenterology)
Abstract Background Sarcopenia is common in chronic pancreatitis (CP) and has been associated with unfavorable outcomes; however, it is not well studied in acute pancreatitis (AP). Aims To evaluate risk factors for sarcopenia among individuals with AP or CP. Methods A cross sectional analysis was performed among subjects with AP or CP seen in a tertiary care Pancreas Clinic. TeraRecon software was used to calculate the cross-sectional area of skeletal muscle, visceral fat, and subcutaneous fat at the level of the L3 vertebrae. Sarcopenia was classified using sex-specific skeletal muscle index. Univariate and multivariate logistic regressions were performed to assess differences between groups and associations with sarcopenia. Results A total of 49 subjects with AP and 54 subjects with CP were included. Sarcopenia was more frequently observed in CP compared to AP (83.3% vs. 46.9%, p < 0.001). The multivariate logistic regression demonstrated CP, male sex, increased age, and decreased subcutaneous fat were independently associated with sarcopenia. Conclusion Sarcopenia is observed in both CP and AP. In addition to traditional risk factors (including male sex, older age, and decreased subcutaneous fat), CP is independently associated with sarcopenia. Further investigations are necessary to gain deeper insights into sarcopenia pathogenesis, which could inform potential intervention strategies.